Bioinformatics analysis of genes of Streptomyces xinghaiensis (fradiae) ATCC 19609 with a focus on mutations conferring resistance to oligomycin A and its derivatives. (September 2020) - Vatlin, Aleksey A.; Bekker, Olga B.; Lysenkova, Ludmila N.; Shchekotikhin, Andrey E.; Danilenko, Valery N.
Highlights: Mutants of Streptomyces xinghaiensis ( fradiae ) ATCC 19609 resistant to oligomycin A were obtained. Seven mutations were found leading to resistance to oligomycin A and its derivatives in streptomycetes. Non-homologous end joining may be involved in the development of resistance to oligomycin A and its derivatives. Abstract: Objectives: The aim of this study was to obtain Streptomyces xinghaiensis ( fradiae ) ATCC 19609 mutants resistant to oligomycin A and its derivatives and to identify the underlying mechanism of resistance. This study was based on the premise that S. xinghaiensis ATCC 19609 contains several oligomycin A biological targets, explaining why the strain remains supersensitive to oligomycin A despite all efforts to obtain resistant mutants using standard genetic methods. Methods: The method to obtain oligomycin A-resistant mutants was performed in two steps: first, mutants slightly resistant to an oligomycin A derivative with an attenuated effect were obtained; and second, oligomycin A-resistant mutants were obtained from those mutants obtained earlier. The genomes of the mutants were then sequenced and a bioinformatics analysis of the detected mutations was conducted. Results: Mutants with seven mutations were required to obtain oligomycin A-resistant mutant strains of S. xinghaiensis characterised by a level of resistance comparable with that of the model organism Streptomyces lividans. Five of these mutations caused amino acid substitutions in the well-known oligomycin A biological target, namely the F0F1-ATP synthase A subunit, and the others caused amino acid substitutions in unexplored biological targets, including RecB-like recombinase, type IV helicase, DNA ligase and single-domain response regulator. Conclusion: A new oligomycin resistance mechanism involving a pathway that repairs double-strand breaks in DNA known as non-homologous end joining (NHEJ) was discovered.